Certain Aspects of Legal Regulation of Essential Conditions of the Constituent (Founding) Agreement in Full and Limited Partnerships - Gapolyak , Taras (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The scientific article explores the problems of legal regulation of the essential conditions of the constituent (founding) agreement of the whole and commanding societies. It is indicated by a superficial comparison with the requirements for the content of the constituent documents of joint stock companies, limited liability companies, and companies with additional liability and the absence in the norms of the current legislation of a clear list of essential conditions of the founding agreement of full and limited companies. It indicates the expediency of determining at the level of special legislation the consolidated list of essential conditions of the founding agreement, in particular:conditions on the obligation of the founders to create a company, conditions on the procedure for the joint activities of the founders to create a company, conditions for transferring property to the company; conditions on the type of partnership, subject matter, purpose of activity, and name of the economic partnership; terms on the term of the economic partnership; terms and conditions on the accumulated capital, the size, and procedure for changing the shares of participants, the total amount of deposits of depositors in the memorandum of association; conditions on the procedure for participation of participants in the affairs of the company and the management of the company; conditions for the distribution of profits and losses of the entire company; conditions on changes in the membership of the entire company; terms and conditions of liquidation and reorganization of the company; other conditions that do not contradict the current legislation of Ukraine. It is concluded that the conditions on the procedure for conducting business in the founding agreement (agreement on the establishment) of the total and limited partnerships are one of the essential conditions of this agreement, which have their regulation on the level as provisions of the Civil Code of Ukraine and are developed in the provisions of the Law of Ukraine "On Business Associations"; it is emphasized on the combination of imperative and dispositiveness when choosing the format of doing business by participants of entire and teamwork societies with a tendency to the possibility of a dispositivity solution to this issue in the founding agreement. It emphasizes the expediency of revising existing approaches and providing the founders of limited partnerships with the opportunity to determine the scope of powers of each participant and depositor at their own discretion. The need is argued at the legislative level to establish the period during which the participants of the full company undertake to make contributions to the capital of the company - within a year from the date of state registration of the company—and provide for the participants’ responsibility for not making deposits.